Insurgency and Human Security Challenges in Nigeria: Borno State in Perspective - Mohammed, Ngozi Thelma (NIU Journal of Humanities; Vol 5 No 1 (2020): KIU Journal of Humanities, Vol. 5 No. 1, March 2020, 2020)
Boko Haram's recent wave of terrorist attacks marked by the abduction and killing of people; the destruction of homes, classrooms, health centres, churches, mosques, and farms has plunged the nation into a persistent state of insecurity. Therefore the Boko Haram insurgency has threatened the basics of food, safety, shelter, education and defence that primarily constitute security for the human person. To achieve the objectives of this study, a concise and exploratory approach, using a historical method of study and content analysis was adopted. The study reveals how the Boko Haram uprising has culminated in a horrible humanitarian situation evident from human deaths, human rights abuses, population displacement and refugee fiasco, economic crisis, and general insecurity–poorly depicting Nigeria's human health. Furthermore, the paper discusses the challenges to human security in Nigeria from the Boko Haram insurgency with Borno state as its focal point. Findings show that insurgency has claimed many lives and property; has exacerbated the country's food and nutrition insecurity situation; helped spread infectious diseases; denied access to education to millions of children and young people; increased the number of internally displaced persons in desperate need of shelter, and more importantly forced people to live in constant terror and uncertainty. This paper concludes that the Boko Haram Insurgency has a negative impact on human security, and recommends that counterinsurgency can only be successful when poverty, corruption and bad governance problems are handled effectively. Keywords: security, human security, insurgency, counter insurgency